PENGARUH MICRO WAVE DIATHERMY DAN RHYTMICAL STABILISASI TERHADAP PERUBAHAN FUNGSIONAL SENDI LUTUT PENDERITA OSTEOARTRITIS DI BAGIAN FISIOTERAPI RMC MAKASSAR - Suriani Suriani; Suharto Suharto (Politeknik Kesehatan Makassar, 2017)
Osteoarthritis is a chronic disease of cartilage, associated with secondary changes in cartilage, leading to joint inflammation and degeneration. Problems of pain and movement limitations can lead to decreased muscle strength as well as functional impairment in the knee joint, especially walking and up and down stairs. The purpose of this study was to determine whether there is an influence between MWD and Rhytmical Stabilization to functional changes in knee joints in osteoarthritis patients in physiotherapy RMC Makassar. This research is a pre experimental study with pretest-post test design one group design. Research subjects as many as 10 people who have knee osteoarthritis who went to the physiotherapy of Ratulangi Medical Center Makassar. Sampling by accidental sampling during the study was conducted. The results showed a significant difference before - after administration of MWD and Rhitmical stabilization to functional ability of patient walking knee osteoarthritis with average difference of 2.00 cm ± 0,00 with Wilcoxon Signed Ranks Test test p = 0,002 and for functional capability up and down ladder obtained by difference of mean equal to 1,10 ± 0.316 with p = 0.002. The conclusion of this study is the increase in walking ability and up and down stairs of patients with knee osteoarthritis after given MWD and Rhitmical stabilization.